Heart rate threshold is not a valid estimation of the lactate threshold - Parker, D.; Robergs, R. A.; Quintana, R.; Frankel, C. C.; Dallam, G. (Medicine & Science in Sports & Exercise, 1997)
This study assessed the validity of using heart rate threshold during incremental cycle ergometry to represent lactate threshold and steady state heart rate and VO2 during 30 minutes of intense cycle ergometry. Ss (M = 11; F = 9) performed two exercises, one an incremental cycling test and the other a constant isokinetic test. Blood and gases were sampled each minute of each exercise. It was found that VO2max, lactate threshold (%VO2max), or training status (miles/week) significantly contributed to the variance in heart rate threshold. Heart rate threshold is not a valid estimate of lactate threshold when applied to individuals of varied fitness. The deflection point from linearity in heart rate is caused by factors unrelated to the metabolic events contributing to the lactate threshold or VO2max. Implication. Heart rate is not an appropriate index for lactate threshold. The simple procedure of taking heart rates and having them indicate the type of training (e.g., lactate threshold, aerobic) contains too much error to be of any value to individuals participating in important behaviors in practical situations.